Editors' Note: Detection of Cerebral Microbleeds With Venous Connection at 7-Tesla MRI. (26th October 2021) - Siegler, James E.; Galetta, Steven
Abstract : The etiology of cerebral microhemorrhages was further explored in the recently published observational cohort of 51 people who underwent 7T magnetic resonance imaging (MRI), as reported by Dr. Rotta et al . Using Quantitative Susceptibility Mapping of healthy elderly adults and adults with cerebral amyloid angiopathy (CAA) and hypertensive vasculopathy, the investigators observed a disproportionate burden of microbleeds with venous connections among patients with CAA vs control groups. This observation might suggest that some of these microbleeds have a venous origin. Although microbleeds in association with a venous connection represented a minority of microbleeds (only 14%), they were strongly tied to CAA over other conditions. Drs. Chen and Wang commented that cortical vessels may be mistaken for lobar microbleeds, leading to a misclassification bias. Furthermore, Drs. Chen and Wang observed a higher prevalence of deep microbleeds in association with a venous connection in their previous autopsy study. The investigators affirm that these results warrant validation using histopathology. Furthermore, one reason for their unique observations may be the higher sensitivity for detecting microbleeds when using an MRI with a greater magnet strength.